The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.23937/2469-584x/1510083
|View full text |Cite
|
Sign up to set email alerts
|

Altered Mental Status as the Primary Presentation of Stercoral Colitis

Abstract: Past medical history was significant for dementia and cerebrovascular accident (CVA). On admission, the patient's family was concerned regarding her acute change in mentation given her history of CVAs. Her vitals were significant for tachycardia to 103 beats per minutes. Her labs revealed leukocytosis of 23.4 thousand/mm 3 . Given AMS, Computed tomography (CT) head was obtained which revealed no evidence of acute intracerebral event. CT abdomen was also obtained given her abdominal pain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the ED, SC is typically a radiologic diagnosis. While it should be considered in any patient with chronic constipation and abdominal pain, clinical diagnosis is made challenging by the fact that patients often present with vague signs and symptoms, or they may be altogether asymptomatic [ 1 4 ]; in fact, recent literature has reported that 60% of SC patients in the ED denied any abdominal pain [ 5 ]. Computed Tomography (CT) imaging and clinical intuition are therefore critical to the diagnosis of SC, and several studies have described radiologic findings important for the detection of SC and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…In the ED, SC is typically a radiologic diagnosis. While it should be considered in any patient with chronic constipation and abdominal pain, clinical diagnosis is made challenging by the fact that patients often present with vague signs and symptoms, or they may be altogether asymptomatic [ 1 4 ]; in fact, recent literature has reported that 60% of SC patients in the ED denied any abdominal pain [ 5 ]. Computed Tomography (CT) imaging and clinical intuition are therefore critical to the diagnosis of SC, and several studies have described radiologic findings important for the detection of SC and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age, dementia, chronic concomitant illness, cancer, and non-ambulatory status are all risk factors for stercoral colitis, with persistent constipation of any kind being the predominant predisposing condition [ 4 ]. Chronic neurologic and psychiatric illnesses may delay the diagnosis of SC because they hinder thorough history-taking and conceal physical examination findings [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a complication of what initially appeared as simple constipation. Early identification and treatment of stercoral colitis are essential to reduce overall morbidity and mortality [ 4 ]. The incidence of SC is predicted to rise with the aging of our population; thus, clinicians need to be aware of this illness, key diagnostic tools, and treatment options [ 4 ].…”
Section: Introductionmentioning
confidence: 99%